Baseline patients' characteristics as predictors for therapeutic survival and response in patients with psoriasis on biological treatments. (8th January 2018) - Xie, Kenneth K; Braue, Anna; Martyres, Raymond; Varigos, George
Abstract: Background/Objectives: Biological agents provide a relatively safe and promising long‐term therapeutic option for patients with moderate to severe psoriasis in whom conventional treatment has failed. However, these agents are not effective in all patients. We aimed to examine the association of baseline patients' characteristics with the short‐term efficacy and the long‐term survival of biological therapies in patients with moderate to severe psoriasis. Methods: We performed a retrospective observational study of all patients who received biological treatment for psoriasis at the Royal Melbourne Hospital ( N  = 146). We extracted data on the patients' characteristics and medical history. The outcomes we measured included a 75% reduction in psoriasis area and severity index (PASI) score at 12 and 24 weeks, the total duration of drug survival and dermatology life quality index (DLQI) scores. We used regression modelling to assess the association between each baseline patient's characteristic and outcome measures. Results: An increase in baseline body mass index was associated with a reduced likelihood of achieving PASI75 at 12 and 24 weeks ( P  =   0.014) and also correlated with reduced long‐term therapeutic survival ( P  =   0.03). High rates of treatment termination were noted in patients with greater baseline DLQI ( P  =   0.038). Conclusion: Greater body mass index at the initiation of biological treatment for psoriasis may contribute to its decreased short‐term efficacy. Similarly, a high body mass index or DLQI at baseline was associated with a relatively short duration of biological treatment retention.